2014
DOI: 10.1097/ta.0000000000000244
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcome of patients with blunt splenic injury and preexisting liver cirrhosis

Abstract: Prognostic/epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The use of prothrombotic agents or fibrinolysis inhibitors is not specifically addressed in this study; although given the inherent thrombophilia of liver failure patients, the associated thrombotic risk may be much more significant than the general population. 25,26 Although the retrospective nature of this study limits our ability to fully clarify the difference between failed NOM and primary splenectomy, this rate of splenectomy in patients with cirrhosis and BSI is much higher than the 17% failure rate reported in an NTDB study reported by Bugaev et al, but somewhat less than the 92% failure rate reported in a 12 patient series by Fang et al 13,14 The higher than usual splenectomy rate observed in the control population may be an artifact of the 20-year period of the study, or may be an artifact of selecting control patients to match cirrhotic patients with significant splenic injuries. Our case and control populations had a greater than 50% incidence of high-grade splenic injuries, and these patients are presumably at a higher risk of failing NOM than populations that include a lower incidence of high-grade splenic injuries.…”
Section: Commentsmentioning
confidence: 54%
See 4 more Smart Citations
“…The use of prothrombotic agents or fibrinolysis inhibitors is not specifically addressed in this study; although given the inherent thrombophilia of liver failure patients, the associated thrombotic risk may be much more significant than the general population. 25,26 Although the retrospective nature of this study limits our ability to fully clarify the difference between failed NOM and primary splenectomy, this rate of splenectomy in patients with cirrhosis and BSI is much higher than the 17% failure rate reported in an NTDB study reported by Bugaev et al, but somewhat less than the 92% failure rate reported in a 12 patient series by Fang et al 13,14 The higher than usual splenectomy rate observed in the control population may be an artifact of the 20-year period of the study, or may be an artifact of selecting control patients to match cirrhotic patients with significant splenic injuries. Our case and control populations had a greater than 50% incidence of high-grade splenic injuries, and these patients are presumably at a higher risk of failing NOM than populations that include a lower incidence of high-grade splenic injuries.…”
Section: Commentsmentioning
confidence: 54%
“…This surrogate has been previously used given the challenges with evaluating the true surgical intent on retrospective review. 14 We found no statistical difference in the frequency of immediate splenectomy between patients with cirrhosis [64% (25/39)] and control patients [47% (43/91), P 5 .88].…”
Section: Splenic Interventionmentioning
confidence: 72%
See 3 more Smart Citations